Rucaparib: the past, present, and future of a newly approved PARP inhibitor for ovarian cancer - Dockery, LE (Onco Targets Ther, 2017)
Rucaparib camsylate (CO-338, AG-014699, PF-01367338) is a potent PARP-1, PARP-2, and PARP-3 inhibitor. Phase I and II studies demonstrated clinical efficacy in both BRCA-mutated (inclusive of germline and somatic) ovarian tumors and ovarian tumors with homologous recombination deficiency (HRD) loss of heterozygosity (LOH). Rucaparib has received the US Food and Drug Administration (FDA) approval for patients with deleterious BRCA mutation (germline and/or somatic)-associated advanced ovarian cancer who have been treated with two or more chemotherapies. There is evidence to suggest that rucaparib has clinical efficacy against ovarian tumors with high HRD-LOH. Rucaparib’s companion diagnostic FoundationFocus™ CDx(BRCA) test is the first FDA-approved next-generation sequencing-based companion diagnostic test designed to identify patients likely to respond to rucaparib. This article reviews the mechanisms of action, safety, approval, and indications for use of the PARP inhibitor rucaparib as well as future trials and use of rucaparib’s companion diagnostic test.